Natural Killer Cells in Antifungal Immunity - Schmidt, Stanislaw; Tramsen, Lars; Lehrnbecher, Thomas (Frontiers in Immunology, 2017)
Invasive fungal infections are still an important cause of morbidity and mortality in immunocompromised patients such as patients suffering from hematological malignancies or patients undergoing hematopoietic stem cell transplantion. In addition, other populations such as HIV-patients are at higher risk for invasive fungal infection. Despite the availability of new antifungal compounds and better supportive care measures, the fatality rate of invasive fungal infection remained unacceptably high. It is therefore of major interest to improve our understanding of the host-pathogen interaction in order to develop new therapeutic approaches such as adoptive immunotherapy. As experimental methodologies have improved and we now better understand the complex network of the immune system, the insight in the interaction of the host with the fungus has significantly increased. It has become clear that host resistance to fungal infections is not only associated with strong innate immunity, but that adaptive immunity (e.g., T cells) also plays an important role. The antifungal activity of Natural Killer (NK) cells has been underestimated for a long time. In vitro studies demonstrated that NK cells from murine and human origin are able to attack fungi of different genera and species. NK cells exhibit not only a direct antifungal activity via cytotoxic molecules, but also an indirect antifungal activity via cytokines. However, it has been show that fungi exert immunosuppressive effects on NK cells. Whereas clinical data are scarce, animal models have clearly demonstrated that NK cells play an important role in the host response against invasive fungal infections. In this review we summarize clinical data as well as results from in vitro and animal studies on the impact of NK cells on fungal pathogens.